Migration of photoinitiators, phthalates and plasticizers from paper and cardboard materials into different simulants and foodstuffs. (15th May 2021) - Blanco-Zubiaguirre, L.; Zabaleta, I.; Prieto, A.; Olivares, M.; Zuloaga, O.; Elizalde, M.P.
Highlights: Migration of contaminants from cardboards to foodstuffs and simulants was studied. 50% and 95% EtOH were used as simulants at different contact times and temperatures. Migration of targets to 50% EtOH seemed to depend on water solubility and log Kow. Migration from baking paper to tenax at 150 °C was high and increased at 250 °C. Tenax mimicked migration to rice and cereals, 95% EtOH was suitable for milk powder. Abstract: The migration of photoinitiators, phthalates and plasticizers from two paper and cardboard materials into food simulants (50% and 95% EtOH and Tenax) and foodstuffs (rice, cereals and milk powder) was studied. In the case of liquid simulants migration was observed to reach the equilibrium after 60 min and depended on the material type and the physicochemical parameters of the migrants, whereas the temperature (room temperature and 60 °C) did not show significant effects. The study of migration of the compounds from a baking paper to Tenax at high temperatures (150 and 250 °C) evidenced an increment of migration when increasing temperature, except for the most volatile analytes. Finally, the migration to foodstuffs was studied using fully validated analytical protocols. Overall, the comparison of the migration rates demonstrated that Tenax was adequate for the simulation of the migration to rice and cereals, but underestimated the migration to infant milk powder, for which 95% EtOH resulted a more suitable simulant.